Acute Diarrhoea in Children: Determination of Duration Using a Combined Bismuth Hydroxide Gel and Oral Rehydration Solution Therapy vs. Oral Rehydration Solution - Adriana Oviedo; Mirna Díaz; María Laura Valenzuela; Victoria Vidal; Liliana Racca; Hebe Bottai; Graciela Priore; Graciela Peluffo; Susana Di Bartolomeo; Graciela Cabral; María del Carmen Toca (MDPI AG, 2016)
Oral rehydration salt (ORS) treatment in young children with acute diarrhoea (AD) has contributed to decrease mortality associated with dehydration although effective strategies to reduce morbidity associated with this disease are required. The aim of this study was to evaluate the diarrhoea duration when using combined colloidal bismuth hydroxide gel (CBHG) and oral rehydration salt treatment compared with ORS therapy in children with AD. We designed a double-blind, randomised prospective study with treatment and control groups. Patients aged one to 12 years, with no prior pathology and with AD of less than 48 h were included. The Chi-squared and Mann-Whitney tests were used, as well as the Cox proportional hazards model and the Kaplan-Meier estimator. Patients were randomised into an ORS and CBHG treatment group and a control group for ORS plus placebo. (Average age: 3.2 years). The result of the post-treatment evaluation with respect to the average duration of AD was 25.5 h for the treated group vs. 41.5 h for the control group (p = 0.015). The average number of stools was 4.8 in the treated group and 8.2 in the control group (p = 0.032). We conclude that the use of CBHG plus ORS significantly reduced the duration of AD, the number of stools and the percentage of children with persistent AD after 24 h of treatment compared to the control group. AD remitted almost twice as fast in patients treated with CBHG and ORS compared to those who received ORS plus placebo.